Does osteotomizing the lower border of the mandible affect the lingual split pattern in a sagittal split ramus osteotomy? - Alah Dawood Al-Dawoody; Shehab Ahmed Hamad; Khurshid A. Kheder Khrwatany; Twana Hoshyar Saleem (Head & Face Medicine, 2023)
Abstract Aim The purpose of this study was to evaluate the effect of adding a fourth osteotomy at the lower border of the mandible on the lingual cortical fracture pattern in bilateral sagittal split ramus osteotomies. Patients and methods The sample of the study consisted of 20 patients (12 male and 8 female, with a mean age of 26.79 ± 7.12 years) with mandibular deformities who needed bilateral sagittal split ramus osteotomy. One side underwent a traditional sagittal split ramus osteotomy, and the procedure was modified on the other side by adding a 1 cm horizontal osteotomy at the lower border of the mandible, just distal to the caudal end of the vertical buccal osteotomy cut. A 3D CBCT was used to identify the split pattern. Results In the total sample, 40% of the lingual splits ran vertically toward the lower border of the mandible (LSS1), 20% of the splits passed horizontally to the posterior border of the mandible (LSS2), 32.5% of the splits took place along the inferior alveolar canal (LSS3), and 7.5% of the splits were unfavourable fractures (LSS4). On the inferior border osteotomy sides, the distribution of LSS1, LSS2, LSS3, and LSS4 was 10 (25%), 6 (15%), 4 (10%), and 0 (00), respectively. Their distribution on the sides without inferior border osteotomy was 6 (15%), 8 (20%), 13 (32.5%), and 3 (7.5%), respectively. Statistical analysis revealed a significant difference between the two groups (p < 0.05). Conclusion Inferior border osteotomy tends to direct the lingual split fracture line toward the lower and posterior borders of the mandible and minimizes bad splits; however, further studies are needed to confirm our findings.